2018
DOI: 10.24990/injec.v2i1.15
|View full text |Cite
|
Sign up to set email alerts
|

The Provison of Orientation to the Anxiety Levels of the New Patient at the Ponek (Obgyn) General Hospital Jombang

Abstract: ABSTRAKPendahuluan. Pasien yang baru pertama kali masuk ke Rumah Sakit biasanya mengalami kecemasan karena lingkungan Rumah Sakit sangat berbeda dengan lingkungan mereka selama ini. Tujuan penelitian ini adalah menganalisis pengaruh pemberian orientasi terhadap tingkat kecemasan pada pasien baru di Ruang PONEK RSUD Jombang. Metode. Jenis penelitian yang digunakan adalah penelitian eksperimen kuasi dengan before and after with control design. Jumlah sampel untuk kelompok eksperimen 30 subjek penelitian dan kelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Patients that are hospitalized for the first time usually experience anxiety because the hospital is different from their regular environment. 1,2 They can also experience stress-inducing situations during treatment. 3 Furthermore, a survey by the Agency for Health Research and Quality (AHRQ) on 100 new patients reported that 75% experienced acute stress in the first 24-48 hours of hospitalization, while 25% adapted to the condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients that are hospitalized for the first time usually experience anxiety because the hospital is different from their regular environment. 1,2 They can also experience stress-inducing situations during treatment. 3 Furthermore, a survey by the Agency for Health Research and Quality (AHRQ) on 100 new patients reported that 75% experienced acute stress in the first 24-48 hours of hospitalization, while 25% adapted to the condition.…”
Section: Introductionmentioning
confidence: 99%
“…3 Furthermore, a survey by the Agency for Health Research and Quality (AHRQ) on 100 new patients reported that 75% experienced acute stress in the first 24-48 hours of hospitalization, while 25% adapted to the condition. 1 Inpatient often face many unknown and complicated procedures, which causes mild level to severe anxiety and fear. 3 It was then assumed that these problems occurred due to a lack of proper orientation by the nurses.…”
Section: Introductionmentioning
confidence: 99%